Adipose-Derived Mesenchymal Stem Cell Application Combined With Fibrin Matrix Promotes Structural and Functional Recovery Following Spinal Cord Injury in Rats - Mukhamedshina, Yana O.; Akhmetzyanova, Elvira R.; Kostennikov, Alexander A.; Zakirova, Elena Y.; Galieva, Luisa R.; Garanina, Ekaterina E.; Rogozin, Alexander A.; Kiassov, Andrey P.; Rizvanov, Albert A. (Frontiers in Pharmacology, 2018)
The use of stem and progenitor cells to restore damaged organs and tissues, in particular, the central nervous system, is currently considered a most promising therapy in regenerative medicine. At the same time, another approach aimed at stimulating regeneration with the use of stem cells encapsulated into a biopolymer matrix and capable of creating a specific microenvironment for the implanted cells similar to the natural extracellular matrix is under active development. Here we study effects of the application of adipose-derived mesenchymal stem cells (AD-MSCs) combined with a fibrin matrix on post-traumatic reactions in the spinal cord in rats. The AD-MSC application is found to exert a positive impact on the functional and structural recovery after spinal cord injury (SCI) that has been confirmed by the results of behavioural/electrophysiological and morphometric studies demonstrating reduced area of abnormal cavities and enhanced tissue retention in the site of injury. Immunohistochemical and real-time PCR analyses provide evidence that AD-MSC application decreases the GFAP expression in the area of SCI that might indicate the reduction of astroglial activation. Our results also demonstrate that AD-MSC application contributes to marked upregulation of PDGFβR and HSPA1b mRNA expression and decrease of Iba1 expression at the site of the central canal. Thus, the application of AD-MSCs combined with fibrin matrix at the site of SCI during the subacute period can stimulate important mechanisms of nervous tissue regeneration and should be further developed for clinical applications.